Photocatalytic decarboxylative allylation of α-amino acids and peptides under metal-free conditions - Zhang, Yinlei (2024)
We developed an organophotoredox catalytic system to facilitate the decarboxylative allylation coupling process concerning α-amino acids and related C-terminal carboxylate peptides using Morita-Baylis-Hillman adducts as allylic precursors. This metal-free method operates under mild conditions and is compatible with various amino acids. The versatility of this protocol, particularly in chemical biology research, has been preliminarily demonstrated through the ligation of bioactive peptide chains.